Polymer film loaded with lithium-intercalated graphite, preparation method and application of polymer film, and lithium ion battery containing silicon negative electrode
By using a polymer film separator with lithium-ion state embedded in lithium-ion batteries, the problem of volume expansion of silicon negative electrode during circulation is solved, and higher Coulomb efficiency and cycle stability are achieved.
Patent Information
- Application Number
- CN202411823183.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-12
AI Technical Summary
The silicon negative electrode will expand volumetrically during the circulation of lithium-ion batteries, resulting in interface side reactions, reducing Coulomb efficiency and damaging cycling stability.
A polymer film loaded with lithium-embedded graphite is used as a separator, which consists of a polymer microporous film and a lithium-embedded graphite layer bonded to the surface of either side thereof. As a porous rough coating, the lithium-embedded graphite layer includes components such as LiC6, LiC12, LiC18, and LiC24, which can provide support and suppress particle displacement and cracks when the silicon negative electrode expands.
It effectively suppresses the volume expansion of the silicon negative electrode, improves the Coulomb efficiency and cycle stability of lithium-ion batteries, and significantly improves the battery performance.
Smart Images

Figure CN119764759A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion batteries, and specifically relates to a polymer film loaded with lithium-intercalated graphite, a preparation method and application thereof, and a lithium ion battery containing a silicon negative electrode. Background Art
[0002] With the rapid development of electronic portable devices and electric vehicles, it is particularly important to research and develop high-performance lithium-ion batteries. Silicon anodes have extremely high theoretical specific capacity, which is more than ten times that of traditional graphite anodes. The high specific capacity and safety of silicon (Si) anodes have attracted widespread attention in the application of high-energy, high-power density lithium-ion batteries (LIBs). However, silicon particles will undergo a large amount of volume expansion during the cycle, causing interfacial side reactions, which in turn leads to a decrease in the Coulombic efficiency (CE) of lithium-ion batteries and impaired cycle stability. Summary of the invention
[0003] In view of this, the purpose of the present invention is to provide a polymer film loaded with lithium-intercalated graphite, a preparation method and application thereof, and a lithium-ion battery containing a silicon negative electrode. The polymer film loaded with lithium-intercalated graphite can inhibit the volume expansion of the silicon negative electrode and improve the coulombic efficiency and cycle stability of the lithium-ion battery containing a silicon negative electrode.
[0004] In order to achieve the above object, the present invention provides the following technical solutions:
[0005] The present invention provides a polymer membrane loaded with lithium-intercalated graphite, comprising a polymer microporous membrane and a lithium-intercalated graphite layer bonded to the surface of either side of the polymer microporous membrane; the lithium-intercalated graphite layer is a porous rough coating;
[0006] The lithium-embedded graphite layer includes LiC6, LiC 12 ,LiC 18 and LiC 24 One or more of the .
[0007] Preferably, the polymer microporous membrane is a polypropylene / polyethylene composite microporous membrane.
[0008] Preferably, the pore size of the polymer microporous membrane is 5 to 200 nm; the thickness of the polymer microporous membrane is 10 to 30 μm.
[0009] Preferably, the thickness of the lithium-intercalated graphite layer is 10 to 30 μm.
[0010] The present invention also provides a method for preparing a polymer film loaded with lithium-intercalated graphite according to the above technical solution, comprising the following steps:
[0011] After coating a slurry containing graphite and a binder on one side of the polymer microporous membrane, the slurry is dried to obtain a polymer membrane covered with a graphite coating;
[0012] In an inert atmosphere, the graphite coating side of the polymer film covered with the graphite coating is brought into contact with a lithium negative electrode, and then immersed in an electrolyte to form a primary battery. Short-circuit discharge is performed, and the graphite coating is lithiated to form a lithium-intercalated graphite layer, thereby obtaining the polymer film loaded with lithium-intercalated graphite.
[0013] Preferably, the binder includes one or more of sodium alginate, polyacrylic acid and polyvinylidene fluoride.
[0014] Preferably, the lithium negative electrode is a lithium metal foil; the thickness of the lithium metal foil is 30 to 600 μm.
[0015] Preferably, the short-circuit discharge time is 4 to 10 hours.
[0016] The present invention also provides the use of the polymer film loaded with lithium-intercalated graphite described in the above technical solution or the polymer film loaded with lithium-intercalated graphite prepared by the preparation method described in the above technical solution in a lithium-ion battery containing a silicon negative electrode.
[0017] The present invention also provides a lithium ion battery containing a silicon negative electrode, wherein the diaphragm of the lithium ion battery containing a silicon negative electrode is the polymer film loaded with lithium intercalated graphite described in the above technical solution or the polymer film loaded with lithium intercalated graphite prepared by the preparation method described in the above technical solution.
[0018] The present invention provides a polymer membrane loaded with lithium-intercalated graphite, comprising a polymer microporous membrane and a lithium-intercalated graphite layer bonded to the surface of either side of the polymer microporous membrane; the lithium-intercalated graphite layer is a porous rough coating; the lithium-intercalated graphite layer comprises components of LiC6, LiC 12 ,LiC 18 and LiC 24 One or more of the above. The lithium-intercalated graphite layer in the polymer membrane loaded with lithium-intercalated graphite provided by the present invention serves as a pre-lithium agent for the silicon negative electrode. The lithium-intercalated graphite layer is a porous rough coating. When the silicon is intercalated with lithium to generate a lithium-silicon alloy and softens, the lithium-silicon alloy at the interface will be embedded in the porous rough coating, thereby inhibiting the displacement of silicon negative electrode particles and the generation of cracks. In addition, the silicon negative electrode expands after being intercalated with lithium, and the lithium-intercalated graphite layer is relatively hard (graphite hardens after being intercalated with lithium). The expanded silicon negative electrode and the lithium-intercalated graphite layer squeeze each other, which can effectively limit the expansion of the silicon negative electrode. In addition, the lithium-intercalated graphite layer can also provide additional lithium ions during the cycle process, thereby improving the coulombic efficiency and cycle stability of lithium-ion batteries containing silicon negative electrodes.
[0019] The results of the examples show that when the polymer film (PP / PE@LiC6) loaded with lithium-intercalated graphite provided by the present invention is used as a separator, the initial coulombic efficiency (ICE) of the Si|PP / PE@LiC6|Li button cell reaches 108.51%, and the electrochemical stability is enhanced. In addition, the LiFePO4|PP / PE@LiC6|Si button cell exhibits an ICE of 93.02% and good electrochemical stability at 0.33C (1C = 160A·g -1 ) after 100 cycles, the capacity retention rate was 100.94%, while the average coulombic efficiency (CE) was 99.83%. The present invention provides a safe and easy-to-implement pre-lithiation method for the industrial application of high energy density silicon-based batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 Schematic diagram of the synthesis process of the polymer membrane (PP / PE@LiC6) loaded with lithium-intercalated graphite in Example 1;
[0021] Figure 2 High-resolution SEM image of the polymer film (PP / PE@Gr) coated with graphite in Comparative Example 1 (the inset is an optical image);
[0022] Figure 3 High-resolution SEM image of PP / PE@LiC6 in Example 1 (the inset is an optical image);
[0023] Figure 4 XRD diagrams of PP / PE@Gr in Comparative Example 1 and PP / PE@LiC6 in Example 1;
[0024] Figure 5 The Raman spectra of PP / PE@Gr in Comparative Example 1 and PP / PE@LiC6 in Example 1;
[0025] Figure 6 For comparison, the Si|PP / PE|Li button cell of Application Example 1 is -1 CV curves between 0.01V and 2V (the inset is a schematic diagram of the structure of the Si|PP / PE|Li button battery);
[0026] Figure 7 The Si|PP / PE@LiC6|Li button cell of Application Example 1 is 0.01mV·s -1 CV curves between 0.01V and 2V (the inset is a schematic diagram of the structure of the Si|PP / PE@LiC6|Li button battery);
[0027] Figure 8The first charge and discharge curves of the Si|PP / PE|Li button battery of Application Example 1 and the Si|PP / PE@LiC6|Li button battery of Application Example 1 are compared;
[0028] Fig. 9 dQ / dV curves of the first cycle of the Si|PP / PE|Li button battery of Application Example 1 and the Si|PP / PE@LiC6|Li button battery of Application Example 1 are compared;
[0029] Fig.10 To compare the Si|PP / PE|Li button battery of Application Example 1 and the Si|PP / PE@LiC6|Li button battery of Application Example 1 at 0.1A·g -1 To 2A·g -1 Rate performance diagram when current changes;
[0030] Fig.11 To compare the Si|PP / PE|Li button battery of Application Example 1 and the Si|PP / PE@LiC6|Li button battery of Application Example 1 at 0.5A·g -1 Long-term cycling performance and corresponding Coulombic efficiency diagram under ;
[0031] Fig.12 Electrochemical impedance spectroscopy (EIS) diagram (a) and fitting equivalent circuit diagram (b) of the Si|PP / PE|Li button battery of Application Example 1 and the Si|PP / PE@LiC6|Li button battery of Application Example 1 after 100 cycles;
[0032] Fig.13 A characterization diagram of the surface and thickness changes of the silicon negative electrode in the Si|PP / PE|Li button battery of Application Example 1 and the Si|PP / PE@LiC6|Li button battery of Application Example 1;
[0033] Fig.14 The first charge and discharge curves of the LiFePO4|PP / PE|Si button battery of Application Example 2 and the LiFePO4|PP / PE@LiC6|Si button battery of Application Example 2 are compared;
[0034] Fig.15 At 0.33C (1C = 160A g -1 ) is a comparison chart of the long-term cycle performance and corresponding coulombic efficiency of the LiFePO4|PP / PE|Si button battery of Application Example 2 and the LiFePO4|PP / PE@LiC6|Si button battery of Application Example 2;
[0035] Fig.16 Schematic diagram of the evolution of silicon anode when LiC6 is not coated on PP / PE separator;
[0036] Fig.17 Schematic diagram of the evolution of silicon anode when LiC6 is coated on PP / PE separator. DETAILED DESCRIPTION
[0037] The present invention provides a polymer membrane loaded with lithium-intercalated graphite, comprising a polymer microporous membrane and a lithium-intercalated graphite layer bonded to the surface of either side of the polymer microporous membrane; the lithium-intercalated graphite layer is a porous rough coating;
[0038] The lithium-intercalated graphite layer includes LiC6, LiC 12 ,LiC 18 and LiC 24 One or more of the .
[0039] Unless otherwise specified, the present invention has no special requirements on the sources of the raw materials used, and commercially available products known to those skilled in the art may be used.
[0040] The polymer membrane loaded with lithium-intercalated graphite provided by the present invention comprises a polymer microporous membrane.
[0041] As an embodiment, the polymer microporous membrane includes a polypropylene / polyethylene composite microporous membrane (PP / PE) or a polypropylene diaphragm coated with ceramic particles, and in a specific embodiment, it is a polypropylene / polyethylene composite microporous membrane; the pore size of the polymer microporous membrane is 5 to 200 nm, and in a specific embodiment, it is 20 to 100 nm; the thickness of the polymer microporous membrane is 10 to 30 μm, and in a specific embodiment, it is 20 μm; the model of the polypropylene / polyethylene composite microporous membrane is Canrd 2320.
[0042] The polymer membrane loaded with lithium-intercalated graphite provided by the present invention comprises a lithium-intercalated graphite layer bonded to the surface of either side of the polymer microporous membrane.
[0043] As an embodiment, the lithium-intercalated graphite layer is a porous rough coating.
[0044] As an embodiment, the lithium-intercalated graphite layer comprises LiC6, LiC 12 ,LiC 18 and LiC 24 One or more thereof, in the specific embodiment, it is LiC6.
[0045] As an implementation mode, the thickness of the lithium-intercalated graphite layer is 10 to 30 μm, and in a specific embodiment, it is 20 μm.
[0046] The lithium-intercalated graphite layer in the polymer film loaded with lithium-intercalated graphite provided by the present invention serves as a pre-lithium agent for the silicon negative electrode, and the lithium-intercalated graphite layer is a porous rough coating. When the silicon is intercalated with lithium to generate a lithium-silicon alloy and softens, the lithium-silicon alloy at the interface will be embedded in the porous rough coating, thereby inhibiting the displacement of silicon negative electrode particles and the generation of cracks. In addition, the silicon negative electrode expands after being intercalated with lithium, and the lithium-intercalated graphite layer is relatively hard (graphite hardens after being intercalated with lithium). The expanded silicon negative electrode and the lithium-intercalated graphite layer squeeze each other, which can effectively limit the expansion of the silicon negative electrode, and the lithium-intercalated graphite layer can also provide additional lithium ions during the cycle process, thereby improving the coulombic efficiency and cycle stability of the lithium-ion battery containing the silicon negative electrode.
[0047] The present invention also provides a method for preparing a polymer film loaded with lithium-intercalated graphite according to the above technical solution, comprising the following steps:
[0048] After coating a slurry containing graphite and a binder on one side of the polymer microporous membrane, the slurry is dried to obtain a polymer membrane covered with a graphite coating;
[0049] In an inert atmosphere, the graphite coating side of the polymer film covered with the graphite coating is brought into contact with a lithium negative electrode, and then immersed in an electrolyte to form a primary battery. Short-circuit discharge is performed, and the graphite coating is lithiated to form a lithium-intercalated graphite layer, thereby obtaining the polymer film loaded with lithium-intercalated graphite.
[0050] The invention coats the slurry containing graphite and a binder on one side surface of a polymer microporous membrane and then dries the slurry to obtain a polymer membrane covered with a graphite coating.
[0051] As an embodiment, the graphite is micron graphite powder; the diameter of the micron graphite powder is 10 to 18 μm. In a specific embodiment, the diameter of the micron graphite powder (D 50 )=12μm; the graphite is provided by Shenzhen Eigen Equation Graphene Technology Co., Ltd.
[0052] As an embodiment, the binder includes one or more of sodium alginate, polyacrylic acid and polyvinylidene fluoride, and sodium alginate is used in a specific embodiment; the mass ratio of graphite to binder is 80-97:3-20, and 90-95:5-10 in a specific embodiment; the solvent used in the slurry containing graphite and binder includes one or more of water, N-methylpyrrolidone (NMP) and ethanol, and ethanol is used in a specific embodiment; the mass ratio of the solvent used in the slurry containing graphite and binder to graphite is 0.5-3:1, and 2:1 in a specific embodiment.
[0053] As an implementation method, the coating thickness is 10-30 μm, and in a specific embodiment, it is 20 μm. The present invention has no special limitation on the coating process, as long as the coating can be uniform.
[0054] The coating thickness in the present invention is within the above range, which can avoid too little lithium source provided due to too thin a coating layer, and can also avoid too thick a coating layer, which not only has no effect on improving the first efficiency, but also reduces the overall capacity density of the battery.
[0055] As an implementation mode, the drying temperature is 40 to 120° C., and in a specific embodiment, it is 60 to 80° C.; the drying time is 5 to 24 hours, and in a specific embodiment, it is 10 to 20 hours.
[0056] After the drying, the method further includes cutting. The present invention has no special limitation on the cutting process, and the method can be performed according to actual needs. In an embodiment of the present invention, the cutting is to cut into discs with a diameter of 17 mm.
[0057] After obtaining the polymer film covered with graphite coating, the present invention, in an inert atmosphere, contacts the graphite coating side of the polymer film covered with graphite coating with a lithium negative electrode, immerses them in an electrolyte to form a primary battery, and performs short-circuit discharge. The graphite coating undergoes lithiation to form a lithium-intercalated graphite layer, thereby obtaining the polymer film loaded with lithium-intercalated graphite.
[0058] As an embodiment, the inert atmosphere is an argon atmosphere; the lithium negative electrode is a lithium metal foil; the thickness of the lithium metal foil is 30 to 600 μm, and in a specific embodiment, it is 100 to 500 μm. The concentration of lithium salt affects the rate of short-circuit discharge. If the concentration is too low, the pre-lithiation time will be longer.
[0059] As an embodiment, the electrolyte includes a lithium salt, an organic solvent and an additive; the concentration of the lithium salt in the electrolyte is 0.5-1.5 mol / L, and in a specific embodiment, it is 0.6-1 mol / L; the volume of the additive is 3-7% of the volume of the organic solvent, and in a specific embodiment, it is 5%.
[0060] As an embodiment, the lithium salt includes one or more of lithium hexafluorophosphate (LiPF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium difluorophosphate (LiPO2F2), lithium tetrafluoroborate (LiBF4), lithium bis(oxalate borate) (LiBOB) and lithium difluorooxalate borate (LiODFB), and in a specific embodiment, it is lithium hexafluorophosphate.
[0061] As an embodiment, the organic solvent includes one or more of ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC), and in a specific embodiment, it is ethylene carbonate (EC) and diethyl carbonate (DEC); the volume ratio of ethylene carbonate (EC) to diethyl carbonate (DEC) is 0.5-1.5:0.5-1.5, and in a specific embodiment, it is 1:1.
[0062] As an embodiment, the additive includes fluoroethylene carbonate (FEC) and / or vinylene carbonate (VC), and in a specific embodiment, fluoroethylene carbonate. The additive can form an interface film (SEI) between the negative electrode and the electrolyte.
[0063] As an implementation mode, the short-circuit discharge time is 4 to 10 hours, and in a specific embodiment, it is 5 to 6 hours.
[0064] If the short-circuit discharge time is too short, the pre-lithiation is insufficient and the number of additional lithium ions provided becomes less.
[0065] In an embodiment of the present invention, after the graphite coating side of the polymer film covered with graphite is in contact with the lithium negative electrode, they are immersed in the electrolyte to form a primary battery: the polymer film covered with graphite is placed in the positive electrode shell of the lithium ion battery to ensure that the lithium negative electrode is in contact with the graphite coating side of the polymer film covered with graphite, and then the electrolyte is added to fully immerse the polymer film covered with graphite and the lithium negative electrode; the lithium ion battery is a 2032 battery.
[0066] In the polymer film covered with graphite coating, the graphite layer is the positive electrode and the lithium metal foil is the negative electrode. The two are immersed in an electrolyte to form a primary battery. After short-circuit discharge, the negative electrode lithium metal dissolves and the positive electrode graphite layer is lithiated to form a lithium-intercalated graphite layer, thereby obtaining a polymer film loaded with lithium-intercalated graphite.
[0067] The present invention also provides the use of the polymer film loaded with lithium-intercalated graphite described in the above technical solution or the polymer film loaded with lithium-intercalated graphite prepared by the preparation method described in the above technical solution in a lithium-ion battery containing a silicon negative electrode.
[0068] The present invention also provides a lithium ion battery containing a silicon negative electrode, wherein the diaphragm of the lithium ion battery containing a silicon negative electrode is the polymer film loaded with lithium intercalated graphite described in the above technical solution or the polymer film loaded with lithium intercalated graphite prepared by the preparation method described in the above technical solution.
[0069] As an embodiment, the preparation method of the silicon negative electrode in the lithium ion battery containing the silicon negative electrode comprises the following steps: dispersing nano-Si, carbon black and a binder in water, coating the obtained slurry on a current collector, and cutting after drying to obtain a silicon negative electrode; the particle size of the nano-Si is 50-100nm, and is 80nm in a specific embodiment; the binder is polyacrylic acid (PAA); the mass ratio of the nano-Si, carbon black and binder is 70-94:20-3:10-3, and is 8:1:1 in a specific embodiment; the water is deionized water; the current collector is a copper current collector; the drying temperature is 60-120°C, and is 80°C in a specific embodiment; the drying time is 6-24h, and is 10h in a specific embodiment; the diameter of the silicon (Si) negative electrode is 14mm; the coating density in the silicon negative electrode is 1.0mg·cm -2 The present invention has no special limitation on the cutting process, and it can be performed according to actual needs.
[0070] As an embodiment, the positive electrode of the lithium-ion battery containing silicon negative electrode is a lithium sheet or a LiFePO4 electrode; the preparation method of the LiFePO4 electrode comprises the following steps: dispersing LiFePO4, carbon black and a binder in an organic solvent, coating the obtained slurry on a current collector, and cutting after drying to obtain a LiFePO4 electrode; the binder is polyvinylidene fluoride (PVDF); the organic solvent is N-methylpyrrolidone (NMP); the mass ratio of LiFePO4, carbon black and binder is 70-95:20-2:10-3, and 95:2:3 in a specific embodiment; the current collector is an aluminum current collector; the drying temperature is 90-130°C, and 110°C in a specific embodiment; the drying time is 6-24h, and 10h in a specific embodiment; the diameter of the LiFePO4 electrode is 12mm. The present invention does not specifically limit the cutting process, and it can be carried out according to actual needs.
[0071] As an embodiment, the electrolyte of the lithium-ion battery containing a silicon negative electrode includes a solute, an additive and a solvent; the solute is LiPF6; the concentration of LiPF6 in the electrolyte is 0.8-1.2 mol / L, and is 1 mol / L in a specific embodiment; the additive is fluoroethylene carbonate (FEC); the volume of the additive is 5% of the volume of the solvent; the solvent is ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of 1:1.
[0072] The technical solutions of the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention, but they should not be construed as limiting the protection scope of the present invention.
[0073] Example 1
[0074] (1) Synthesis of polymer film coated with graphite: A graphite film (micron graphite powder provided by Shenzhen Eigenformation Graphene Technology Co., Ltd., with a mass ratio of 9:1) was prepared. 50 )=12μm) and sodium alginate (SA) adhesive slurry (the solvent used is deionized water, and the mass ratio of solvent to graphite is 2:1), and evenly coated on one side surface of polypropylene / polyethylene composite microporous membrane (PP / PE, model Canrd 2320, thickness of 20μm, pore size of 20nm), then dried at 60℃ for 10h to remove the solvent, and then cut out a disc with a diameter of 17mm to obtain a polymer film covered with graphite coating (PP / PE@Gr, graphite coating thickness of 20μm);
[0075] (2) Synthesis of polymer film loaded with lithium-intercalated graphite: 1 mol / L lithium hexafluorophosphate (LiPF6) was dissolved in a mixed solvent (v / v=1:1) of ethylene carbonate (EC) and diethyl carbonate (DEC), and then 5% of the volume of the mixed solvent of fluoroethylene carbonate (FEC) was added as an additive to obtain an electrolyte; in an inert atmosphere glove box, the above-mentioned polymer film coated with graphite was placed in the positive electrode shell of a 2032 battery (lithium-ion battery), ensuring that the lithium metal foil (500 μm thick) was in contact with the graphite coating of the above-mentioned polymer film coated with graphite, and then the electrolyte was added to fully immerse the lithium metal foil and the polymer film coated with graphite to form a primary cell, and after short-circuit discharge for 6 hours, the graphite coating was lithiated to form a lithium-intercalated graphite layer, thereby obtaining a polymer film loaded with lithium-intercalated graphite (PP / PE@LiC6, wherein the thickness of the lithium-intercalated graphite layer was 20 μm).
[0076] Example 2
[0077] The difference from Example 1 is that the mass ratio of graphite to sodium alginate is 95:5.
[0078] Example 3
[0079] The difference from Example 1 is that the mass ratio of graphite to sodium alginate is 85:15.
[0080] Comparative Example 1
[0081] The polymer film (PP / PE@Gr) coated with graphite prepared in Example 1 was used as a comparative example.
[0082] Comparative Example 2
[0083] The difference from Example 1 is that the polypropylene / polyethylene composite microporous membrane is replaced by a polypropylene microporous membrane.
[0084] Comparative Example 3
[0085] The difference from Example 1 is that the thickness of the graphite coating is 5 μm.
[0086] Comparative Example 4
[0087] The difference from Example 1 is that the thickness of the graphite coating is 50 μm.
[0088] Application Example 1
[0089] Nano-Si (80 nm), carbon black and polyacrylic acid (PAA) were dispersed in deionized water at a mass ratio of 8:1:1. The resulting slurry was coated on a copper current collector (copper foil current collector) and dried at 80 °C for 10 h. The resulting slurry was cut to obtain a 14 mm diameter coating with a coating density of 1.0 mg cm -2 Silicon negative electrode;
[0090] The electrolyte consists of a mixed solvent of ethylene carbonate (EC) and diethyl carbonate (DEC) (v / v = 1:1), in which 1 mol / L of LiPF6 is dissolved, and 5% of the volume of the mixed solvent is added with FEC as an additive;
[0091] The polymer film (PP / PE@LiC6) loaded with lithium-embedded graphite prepared in Example 1 was used as a separator, a silicon negative electrode was used as a negative electrode, a lithium sheet was used as a positive electrode, and the above-mentioned electrolyte was assembled into a Si|PP / PE@LiC6|Li button battery, and the N / P ratio was maintained at 1.15.
[0092] The N / P ratio (Negative / Positive) refers to the negative electrode active material gram capacity × negative electrode surface density × negative electrode active material content ratio ÷ (positive electrode active material gram capacity × positive electrode surface density × positive electrode active material content ratio).
[0093] In the half-cell structure, the silicon anode serves as the working electrode and the lithium metal foil serves as the reference electrode.
[0094] Application Example 2
[0095] The difference from Application Example 1 is that a LiFePO4 electrode is used as the positive electrode to obtain a LiFePO4|PP / PE@LiC6|Si button battery; the preparation process of the LiFePO4 electrode is as follows:
[0096] LiFePO4, carbon black and PVDF were dispersed in NMP at a mass ratio of 95:2:3, and the resulting slurry was coated on an aluminum current collector and dried at 110°C for 10 h, and cut to obtain a LiFePO4 electrode with a diameter of 12 mm.
[0097] Comparative application example 1
[0098] The difference from Application Example 1 is that the diaphragm is replaced by the polymer film loaded with lithium-embedded graphite (PP / PE@LiC6) prepared in Example 1 with the polymer film coated with graphite (PP / PE@Gr) of Comparative Example 1 to obtain a Si|PP / PE|Li button battery.
[0099] Comparative Application Example 2
[0100] The difference from Application Example 2 is that the diaphragm is replaced by the polymer film loaded with lithium-embedded graphite (PP / PE@LiC6) prepared in Example 1 with the polymer film coated with graphite (PP / PE@Gr) of Comparative Example 1 to obtain a LiFePO4|PP / PE|Si button cell.
[0101] Performance Testing
[0102] (1) Figure 1 Schematic diagram of the synthesis process of the polymer membrane (PP / PE@LiC6) loaded with lithium-intercalated graphite in Example 1; Figure 2 High-resolution SEM image of the polymer film (PP / PE@Gr) coated with graphite in Comparative Example 1 (the inset is an optical image); Figure 3 High-resolution SEM image of PP / PE@LiC6 in Example 1 (the inset is an optical image); Figure 4 XRD diagrams of PP / PE@Gr in Comparative Example 1 and PP / PE@LiC6 in Example 1; Figure 5 Raman spectra of PP / PE@Gr in Comparative Example 1 and PP / PE@LiC6 in Example 1.
[0103] Depend on Figure 1 It can be seen that in an inert atmosphere glove box, the lithium metal foil was contacted with the graphite coating side of the PP / PE@Gr separator and completely immersed in the electrolyte. After short-circuit discharge, the PP / PE@LiC6 separator was successfully obtained.
[0104] Depend on Figure 2 and Figure 3 It can be seen that the surface morphology of the prepared PP / PE@Gr and PP / PE@LiC6 separators changed significantly after short-circuit discharge, and the graphite surface transitioned from smooth to rough. Figure 2 and Figure 3 The optical images of PP / PE@Gr and PP / PE@LiC6 separators show that the black graphite coating is transformed into brown-yellow LiC6 during short-circuit discharge.
[0105] pass Figure 4The X-ray diffraction (XRD) analysis confirmed the interaction between the graphite coating and the lithium metal foil during the short-circuit discharge process. The diffraction peaks of the PP / PE@LiC6 separator corresponded well to the LiC6 material (JCPDS No.34-1320), indicating that LiC6 was successfully formed.
[0106] Raman spectra of PP / PE@Gr and PP / PE@LiC6 separators are shown in Figure 2. Figure 5 As shown, I D :I G The ratio dropped from 1.06 to 0.2, indicating a significant increase in graphite defects. This observation further confirmed the intercalation of lithium ions within the graphite layers to form LiC6.
[0107] (2) Electrochemical performance test: The electrochemical performance was evaluated at 25°C, and the constant current charge and discharge performance was measured using the LAND CT2001A system. The CHI 760E electrochemical workstation was used to measure the constant current charge and discharge performance at 0.01 mV·s -1 Voltage range is 0.01-2V (vs.Li + The cyclic voltammetry curves were obtained under the conditions of 10 / Li. The electrochemical impedance spectroscopy (EIS) measurements were performed in the frequency range of 0.01 to 105 Hz.
[0108] 1) The electrochemical performance of the Si|PP / PE|Li button cell of comparative application example 1 and the Si|PP / PE@LiC6|Li button cell of application example 1 was evaluated in the voltage range of 0.01-2V. The results are as follows Figures 6 to 11 As shown, Figure 6 For comparison, the Si|PP / PE|Li button cell of Application Example 1 is -1 and CV curves between 0.01V and 2V (the inset is a schematic diagram of the structure of the Si|PP / PE|Li button battery), Figure 7 The Si|PP / PE@LiC6|Li button cell of Application Example 1 is 0.01mV·s -1 and CV curves between 0.01V and 2V (the inset is a schematic diagram of the structure of the Si|PP / PE@LiC6|Li button battery), Figure 8 The first charge and discharge curves of the Si|PP / PE|Li button battery of Application Example 1 and the Si|PP / PE@LiC6|Li button battery of Application Example 1 are compared. Fig. 9 The dQ / dV curves of the first cycle of the Si|PP / PE|Li button battery of Application Example 1 and the Si|PP / PE@LiC6|Li button battery of Application Example 1 are compared. Fig.10To compare the Si|PP / PE|Li button battery of Application Example 1 and the Si|PP / PE@LiC6|Li button battery of Application Example 1 at 0.1A·g -1 To 2A·g -1 Rate performance diagram when current changes, Fig.11 To compare the Si|PP / PE|Li button battery of Application Example 1 and the Si|PP / PE@LiC6|Li button battery of Application Example 1 at 0.5A·g -1 Long-term cycling performance and corresponding Coulombic efficiency under .
[0109] exist Figure 6 In the graph, the oxidation peaks observed at potentials of 0.205 V and 0.548 V correspond to the dealloying process of LixSi, while the reduction peaks observed at potentials of 0.125 V and 0.665 V correspond to the lithiation reaction formation of LixSi alloy and the decomposition of electrolyte into solid electrolyte interface film (SEI), respectively.
[0110] Figure 7 The CV peaks at 0.417 V and 0.654 V indicate that the polarization of the Si|PP / PE@LiC6|Li button cell is significantly reduced compared with that of the Si|PP / PE|Li button cell. In addition, the absence of any observable electrolyte decomposition peaks indicates the formation of SEI on the anode of the Si|PP / PE@LiC6|Li button cell.
[0111] Figure 8 The two samples were compared at 0.1A·g -1 The first charge and discharge curve under the condition of 108.51% was found to be significantly higher than the initial CE of Si|PP / PE@LiC6|Li button battery (90.40%). In addition, the discharge capacity of Si|PP / PE@LiC6|Li button battery (3019mAh·g -1 ) exceeds the discharge capacity of Si|PP / PE|Li button battery (2344mAh·g -1 ).
[0112] The differential capacity diagram (dQ / dV) of Si|PP / PE|Li button cell and Si|PP / PE@LiC6|Li button cell is shown in Fig. 9 Compared with the Si|PP / PE|Li button cell, the peak separation potential of the Si|PP / PE@LiC6|Li button cell is reduced by 26.5 mV, which indicates that the PP / PE@LiC6 separator effectively alleviates the electrochemical polarization, which is consistent with the improved rate performance of the Si|PP / PE@LiC6|Li button cell ( Fig.10 ).
[0113] At 0.5A·g -1 The cycling performance of Si|PP / PE|Li button cell and Si|PP / PE@LiC6|Li button cell was compared at the current density. Fig.11 As shown. The results show that the capacity of the Si|PP / PE|Li button cell decays rapidly after 30 cycles, which is lower than that of the Si|PP / PE@LiC6|Li button cell (the capacity retention rate is 61.21% after 100 cycles). In contrast, the Si|PP / PE@LiC6|Li button cell exhibits excellent cycling stability, with a capacity retention rate of 77.93% after 100 cycles. In addition, the reversible capacity of the Si|PP / PE@LiC6|Li button cell begins to increase after 20 cycles and then remains stable with the increase in the number of cycles. This behavior can be attributed to the volume expansion of Si particles, which leads to enhanced connectivity between the silicon anode and the PP / PE@LiC6 separator, resulting in higher capacity release. In addition, the average CE of the Si|PP / PE|Li button cell and the Si|PP / PE@LiC6|Li button cell are 96.82% and 99.08%, respectively, indicating that the PP / PE@LiC6 separator can continuously provide additional lithium source during the cycling process.
[0114] 2) Fig.12 Electrochemical impedance spectroscopy (EIS) diagram (a) and fitted equivalent circuit diagram (b) of the Si|PP / PE|Li button battery of Application Example 1 and the Si|PP / PE@LiC6|Li button battery of Application Example 1 after 100 cycles.
[0115] Depend on Fig.12 As shown in (a), the Rs, RSEI, and Rct values of the Si|PP / PE|Li button cell are 9.0Ω, 136.4Ω, and 209.5Ω, respectively. In sharp contrast, the Rs, RSEI, and Rct values of the Si|PP / PE@LiC6|Li button cell are 8.6Ω, 55.9Ω, and 8.2Ω, respectively. It is worth noting that after 100 cycles, the Rct of the Si|PP / PE@LiC6|Li button cell is reduced by two orders of magnitude compared with the Si|PP / PE|Li button cell; this finding further confirms the enhanced connectivity between the silicon anode and the LiC6 layer using the PP / PE@LiC6 separator after cycling.
[0116] 3) The surface and thickness changes of the silicon negative electrode in the Si|PP / PE|Li button battery of comparative application example 1 and the Si|PP / PE@LiC6|Li button battery of application example 1 were characterized. Fig.13As shown, the top view SEM image of the silicon negative electrode of Si|PP / PE|Li button battery (a) and Si|PP / PE@LiC6|Li button battery (b) after 100 cycles, the SEM cross-sectional image of the silicon negative electrode of Si|PP / PE|Li button battery (c) and Si|PP / PE@LiC6|Li button battery (d) after 100 cycles, the cross-sectional CT image of the silicon negative electrode of Si|PP / PE|Li button battery (e) and Si|PP / PE@LiC6|Li button battery (f) after 100 cycles, and the pore network model of the silicon negative electrode of Si|PP / PE|Li button battery (g) and Si|PP / PE@LiC6|Li button battery (h) after 100 cycles.
[0117] Fig.13 The top view SEM image in (a) shows obvious cracking in the cycled silicon anode of the Si|PP / PE|Li button cell. Fig.13 (b) shows that the silicon anode of the Si|PP / PE@LiC6|Li button cell maintains a relatively complete electrode structure after 100 cycles without forming any cracks.
[0118] Fig.13 The SEM cross-sectional image in (c) confirms that after 100 cycles, Si particle displacement and electrode cracking occurred in the Si anode of the Si|PP / PE|Li button cell. However, due to the presence of LiC6 coating on the PP / PE separator, Fig.13 In the dense expansion case shown in (d), no electrode cracking was observed after 100 cycles. Fig.13 (e) and Fig.13 The cross-sectional computed tomography (CT) image in (f) also shows that the PP / PE@LiC6 separator effectively protects the integrity of the silicon anode.
[0119] also, Fig.13 Middle (g) and Fig.13 (h) are the pore network models of the silicon negative electrode of Si|PP / PE|Li button battery and Si|PP / PE@LiC6|Li button battery after 100 cycles. In addition, the quantitative evaluation results of the pore throat structure (Table 1) confirmed that compared with the Si|PP / PE|Li button battery, the pore size and pore volume of the silicon negative electrode in the Si|PP / PE@LiC6|Li button battery decreased after 100 cycles. It can be seen that the LiC6 layer on the PP / PE separator effectively inhibits the volume expansion of the silicon negative electrode during the cycle. Table 1 Quantitative evaluation results of the pore throat structure of the silicon negative electrode in Si|PP / PE|Li button battery and Si|PP / PE@LiC6|Li button battery
[0120] project <![CDATA[PP / PE100 th ]]> <![CDATA[PP / PE@LiC6100 th ]]> Maximum pore radius 9.21μm 7.83μm Average pore radius 1.74μm 1.60μm Maximum throat radius 5.77μm 5.38μm Average throat radius 0.92μm 0.78μm Maximum throat length 18.37μm 33.12μm Average throat length 4.2μm 3.53μm Maximum pore-throat ratio 17.5 14.01 Average pore-throat ratio 2.11 2.18 Maximum pore volume <![CDATA[47309μm 3 ]]> <![CDATA[44816μm 3 ]]> Average pore volume <![CDATA[726.75μm 3 ]]> <![CDATA[552.32μm 3 ]]> Maximum throat volume <![CDATA[3981μm 3 ]]> <![CDATA[2758μm 3 ]]> Average throat volume <![CDATA[49.73μm 3 ]]> <![CDATA[18.36μm 3 ]]> Maximum coordination number 32 64 Average coordination number 5 8
[0121] 4) The electrochemical performance of the LiFePO4|PP / PE|Si button cell prepared in Comparative Application Example 2 and the LiFePO4|PP / PE@LiC6|Si button cell prepared in Application Example 2 in the voltage range of 2.2-4.0V (N / P=1.15) was evaluated. Fig.14 The first charge and discharge curves of the LiFePO4|PP / PE|Si button battery of Application Example 2 and the LiFePO4|PP / PE@LiC6|Si button battery of Application Example 2 are compared. Fig.15 At 0.33C (1C = 160A g -1 ) is a comparison chart of the long-term cycle performance and corresponding coulombic efficiency of the LiFePO4|PP / PE|Si button battery of Application Example 2 and the LiFePO4|PP / PE@LiC6|Si button battery of Application Example 2, Fig.16 Schematic diagram of the evolution of silicon anode when LiC6 is not coated on PP / PE separator. Fig.17 Schematic diagram of the evolution of silicon anode when LiC6 is coated on PP / PE separator.
[0122] Fig.14 The two samples were compared at 0.1C (1C = 160A g -1 ) under the first charge-discharge curve, it was found that the initial CE (93.02%) of the LiFePO4|PP / PE@LiC6|Si button cell was significantly higher than that of the LiFePO4|PP / PE|Si button cell (80.97%). In addition, the charge capacity (155mAh·g -1 ) is significantly larger than LiFePO4|PP / PE|Si button battery (126mAh·g -1 ). The cycling performance of LiFePO4|PP / PE|Si button cell and LiFePO4|PP / PE@LiC6|Si button cell at 0.33C current density was compared. Fig.15As shown. The results show that after 100 cycles, the capacity of the LiFePO4|PP / PE|Si button cell decays rapidly, with a capacity retention rate of only 28.22%. In contrast, the LiFePO4|PP / PE@LiC6|Si button cell exhibits excellent cycling stability, maintaining a capacity retention rate of 100.94% after 100 cycles. In addition, the average CE of the LiFePO4|PP / PE@LiC6|Si button cell and the LiFePO4|PP / PE|Si button cell are 99.83% and 98.38%, respectively, indicating that the presence of LiC6 on the PP / PE@LiC6 separator ensures a continuous supply of additional lithium sources during the cycling process.
[0123] Fig.16 and Fig.17 The evolution of silicon anode with and without LiC6 layer on PP / PE separator is described respectively. It is obvious that in the absence of LiC6 layer, the silicon anode undergoes uncontrolled expansion during the cycle, resulting in significant changes in the position of Si particles, promoting electrode cracking, and causing debonding from Si particles to form dead Si with the copper foil current collector. In addition, the excessive growth of SEI hinders the electron transfer between Si particles, resulting in capacity decay. In contrast, coating a layer of LiC6 on the PP / PE separator allows the silicon anode to expand densely, effectively solving the problems of particle displacement and electrode cracking in the silicon anode, while providing additional lithium ions during the cycle.
[0124] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention rather than all the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A polymer film loaded with lithium-intercalated graphite, characterized in that: It comprises a polymer microporous membrane and a lithium-intercalated graphite layer bonded to the surface of either side of the polymer microporous membrane; the lithium-intercalated graphite layer is a porous rough coating; The lithium-embedded graphite layer includes LiC6, LiC 12 ,LiC 18 and LiC 24 One or more of the .
2. The polymer membrane loaded with lithium-intercalated graphite according to claim 1, characterized in that: The polymer microporous membrane is a polypropylene / polyethylene composite microporous membrane.
3. The polymer membrane loaded with lithium-intercalated graphite according to claim 1 or 2, characterized in that: The pore size of the polymer microporous membrane is 5 to 200 nm; the thickness of the polymer microporous membrane is 10 to 30 μm.
4. The polymer membrane loaded with lithium-intercalated graphite according to claim 1, characterized in that: The thickness of the lithium-intercalated graphite layer is 10 to 30 μm.
5. The method for preparing a polymer film loaded with lithium-intercalated graphite according to any one of claims 1 to 4, characterized in that: The following steps are involved: After coating a slurry containing graphite and a binder on one side of the polymer microporous membrane, the slurry is dried to obtain a polymer membrane covered with a graphite coating; In an inert atmosphere, the graphite coating side of the polymer film covered with the graphite coating is brought into contact with a lithium negative electrode, and then immersed in an electrolyte to form a primary battery. Short-circuit discharge is performed, and the graphite coating is lithiated to form a lithium-intercalated graphite layer, thereby obtaining the polymer film loaded with lithium-intercalated graphite.
6. The preparation method according to claim 5, characterized in that: The binder includes one or more of sodium alginate, polyacrylic acid and polyvinylidene fluoride.
7. The preparation method according to claim 5, characterized in that: The lithium negative electrode is a lithium metal foil; the thickness of the lithium metal foil is 30 to 600 μm.
8. The preparation method according to claim 5, characterized in that: The short-circuit discharge time is 4 to 10 hours.
9. Use of a polymer film loaded with lithium intercalated graphite as claimed in any one of claims 1 to 4 or a polymer film loaded with lithium intercalated graphite prepared by the preparation method as claimed in any one of claims 5 to 8 in a lithium ion battery containing a silicon negative electrode.
10. A lithium ion battery containing a silicon negative electrode, characterized in that: The separator of the lithium-ion battery containing a silicon negative electrode is a polymer film loaded with lithium-intercalated graphite as described in any one of claims 1 to 4 or a polymer film loaded with lithium-intercalated graphite prepared by the preparation method as described in any one of claims 5 to 8.
Citation Information
Patent Citations
Batteries utilizing electrode coatings directly on nanoporous separators
CN102460772A
Lithium ion battery capable of being charged at low temperature
CN112290080A
Separation membrane and lithium secondary battery comprising same
EP3667768A1
A carbon coated separator for lithium sulfur batteries
KR1020180020083A
Mahan Gayageum
KR102816909B1